A Metafora pada Lirik Lagu Shinkai Karya Eve Pendekatan Teori Ullman dan Halley - Nugroho, Tri Adhi Yudha; Nur, Tadjuddin (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 6 No 2 (2024)DO - 10.24843/JS.2024.v06.i02.p08, 2024)
This research is titled "Metaphor in Eve's Shinkai song lyrics using Ullman and Halley's theory". This research analyzes the metaphors contained in Eve's song lyrics entitled Shinkai. This research uses Ullman and Halley's metaphor theory and uses descriptive analysis method. The purpose of this study is to explain and describe the use and meaning of metaphors used by the author in the lyrics of the song he composed in this study is the lyrics again titled Shinkai. The lyrics of the song Shinkai contain metaphors that are creatively created by the songwriter and the listeners of the song try to interpret them. The result of this research is that 4 types of metaphors were found, namely anthropomorphic, abstracting, and synesthetic metaphors proposed by Ullman and terrestrial metaphors proposed by Halley. The song uses metaphors to create strong and profound imagery to describe the darkness and despair felt by the subject of the song. These metaphors help listeners to understand complex feelings through more figurative and imaginative language.